2003
DOI: 10.1038/sj.ijir.3901051
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effect of acute and subchronic treatments with Ferula hermonis on copulatory behavior of male rats

Abstract: Sexually potent and sluggish/impotent male rats were orally treated with an extract of Ferula hermonis (30 and 60 mg/kg). The acute administration stimulated sexual motivation in potent rats and improved copulatory performance in sluggish/impotent rats. This last effect was elicited only by the higher dose, which, in parallel, increased serum testosterone levels in rats. On the contrary, when the extract was subchronically administered (10 days) a marked reduction in the percentage of rats achieving ejaculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 11 publications
2
29
1
1
Order By: Relevance
“…5 The results obtained in the present experiments following the acute administration of single components of F. hermonis suggested that ferutinin plays a main role in the improvement of sexual behavior of potent and, more interestingly, of sluggish/ impotent rats. In this context, a significant effect Figure 2 Effect of acute administration of ferutinin, teferdin and teferin on serum testosterone levels in rats.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…5 The results obtained in the present experiments following the acute administration of single components of F. hermonis suggested that ferutinin plays a main role in the improvement of sexual behavior of potent and, more interestingly, of sluggish/ impotent rats. In this context, a significant effect Figure 2 Effect of acute administration of ferutinin, teferdin and teferin on serum testosterone levels in rats.…”
Section: Discussionmentioning
confidence: 61%
“…Rats were trained with sexually receptive females seven times, at 5-day intervals, before the experimental test. As previously described, 5 after the seventh pre-experimental training test, rats that concluded the performance in the last three tests were defined as sexually potent. The remaining rats, which failed to achieve ejaculation in one, two or all the last three pre-experimental tests, were considered sexually sluggish or impotent.…”
Section: Behavioral Testing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of different medicinal plants to improve sexual function (e.g. Tribulus terrestris, Panax ginseng, Ferula hermonis) was ascribed to increased levels of testosterone in the serum (Fahim et al, 1982;Gauthaman et al, 2002;Zanoli et al, 2003) or to an enhanced production of the hormone by Leydig cells (e.g. Ginkgo biloba) (Ye et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Then a sexually receptive female rat was introduced in the cage and the copulatory test started. The following parameters of sexual behavior were measured as previously described by Ågmo (1997) and by Zanoli et al (2003Zanoli et al ( , 2008:…”
Section: Mating Testmentioning
confidence: 99%